Magnetic Resonance Imaging Features of Collet-Sicard Syndrome Associated With Glomus Jugulare Paraganglioma. Issue 6 (September 2019) - Mutlu, Vahit; Ogul, Hayri
Abstract : Abstract: Collet-Sicard syndrome is an unusual disorder. The authors here demonstrated the Magnetic resonance (MR) imaging findings of the Collet-Sicard syndrome associated with glomus jugulare tumor. Neoplastic or non-neoplastic lesion of skull base can cause Collet-Sicard syndrome. MR imaging can be used successfully to demonstrate the etiology of this syndrome.